Are energy Drinks Scapegoats? Decomposing Teenagers' Caffeine intake from Energy Drinks and Soda Beverages. (15th October 2018) - Turel, Ofir
ABSTRACT: Background : Energy drinks have been repeatedly blamed for contributing to caffeine intake among teenagers. Objectives : This study aimed to estimate and compare the caffeine intake of US teenagers from soda drinks versus energy drinks and shots. Methods : Data were taken from a 2015 nationally representative survey (Monitoring the Future) of 8th and 10th graders in the US (47.2% 8th grade; 51.1% female). Participants reported their numbers of consumed sodas, diet sodas, energy drinks, and energy shots per day. These were converted into mg caffeine/day and were contrasted with common guidelines for healthy caffeine intake, stratified by age group and sex. Error-bar charts, ANOVA and ROC curves were used for contrasting caffeine intake from soda drinks and energy drinks, as well as their contribution to exceeding recommended caffeine intake cutoffs. Results : First, in both sexes and grades the intake from soda drinks was significantly higher than the intake from energy drinks. The soda and energy drink intake for males was higher than the intake for females; intake for 8th graders was higher than this of 10th graders. Second, caffeine intake from soda drinks was significantly higher even in those who exceeded the recommended maximum caffeine intake. Third, caffeine intakes from soda and energy drinks were efficacious in explaining the exceeding of the recommended threshold for daily caffeine intake, but the explanatory power of soda drinks was larger. Conclusions : From a caffeine consumption standpoint, health professionals should emphasize reduction in both soda and energy drinks.